OPTIMAL SELECTION OF PROTON PUMP INHIBITOR TREATMENT FOR PREVENTING AND TREATING NSAID-INDUCED GASTROINTESTINAL HARM - Malika Jassim Alhadab, Houson Ali Aloudah, Saleh Bdar Alshammari, Faisal Khalid Naji Alshammari, Owaid Farhan Mashuj Alshammari, Mohammed Shayil Hazzaa Alshammari, Ahmed Hammad Alshammari, Fayez Saleh Alabri Alotaibi,; Nawaf Abdullah Alsaedi, Fouad Ahmed Hassan Al Najei, Jubran Hassan Yahya Alakhan, Miad Fayadh Alanazi (Chelonian Research Foundation, 2023)
NSAIDs can lead to gastrointestinal side effects such as dyspepsia, peptic ulcer disease, and severe consequences like hemorrhage or perforation. This gastrointestinal toxicity is a substantial worldwide medical concern. Misoprostol diminishes NSAID-induced mucosal damage; however its efficacy is constrained by low patient tolerance. Antagonists of histamine receptors are useful in treating duodenal ulcers but not stomach ulcers. Proton pump inhibitors (PPIs) such as pantoprazole, omeprazole, and lansoprazole protect high-risk patients from developing gastric and duodenal ulcers and help in the healing of ulcers caused by NSAIDs. Proton pump inhibitors have a favorable safety profile. Proton pump inhibitors such as lansoprazole, omeprazole, pantoprazole, and rabeprazole are utilized for the treatment of acid-related gastrointestinal conditions such as gastro-esophageal reflux and peptic ulcer disease. All four inhibitors have comparable potency and effectiveness, with Rabeprazole demonstrating a quicker onset of acid inhibition but offering modest therapeutic benefit. Esomeprazole, the S-isomer of omeprazole, is more potent but does not offer any therapeutic benefits. Key Words: proton pump inhibitor, NSAID, ulcer, gastrointestinal